Pelatihan Pembuatan Gluten-Free Brownies Berbasis Tepung Pisang Kepok Sebagai Inovasi Produk Wirausaha bagi Perempuan Usia Produktif di Kota Jayapura - Nurlita Dianingsih; Ika P. Palimbunga; Baiq A. Tartillah; Raini Panjaitan; Erlies P. Ramandey; Jeirel Wattilete; Mika Barasulele (Jurusan Biologi FMIPA Universitas Cenderawasih, 2026)
Banana is one of local commodities widely available in Jayapura City. However, its utilization remains limited and has not been optimally developed into value-added food products. This community service activity aimed to improve the knowledge and skills of productive-age women in processing kepok banana flour into gluten-free brownies as an innovative home-scale business product. The activity was conducted in March 2024 at Rumah BUMN BRI, Jayapura City, and involved approximately 15 female participants, including housewives and adult women with senior high school educational backgrounds who were interested in entrepreneurship but had not yet developed a specific business product. The training consisted of an introduction to banana as a local raw material, explanation of banana flour processing, discussion of business opportunities, and hands-on practice in making brownies using 100% kepok banana flour without wheat flour. Banana flour was prepared before the activity to shorten the training time, while the processing steps were explained in detail to the participants. Evaluation was conducted using pre-test, post-test, and participant satisfaction surveys. The activity produced gluten-free banana flour brownies with various toppings, and participants were actively involved in the preparation, mixing, baking, cutting, and product evaluation processes. Overall, the training improved participants’ understanding and practical skills in utilizing local commodities and introduced banana flour brownies as a potential value-added product for women’s entrepreneurship in Jayapura